Understanding Industrial Transformation Views from Different Disciplines - Olsthoorn, Xander; Wieczorek, Anna J.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2006)
'A system is just like truth's tail, but the truth is like a lizard. It will leave the tail in your hand and escape; it knows that it will soon grow another one.' [Ivan Sergeevich Turgenev (1818-1883), Letter, Paris, January 3, 1857, to Count Lev Nikolaevich Tolstoy. Turgenev: Letters, ed. David] ...a scientist can only come to a partial understanding of industrial transformation processes. This is so not only because of the vastness of the topic, but because of the inherent limitations of each scientific discipline. The common ground, which scientists of different disciplines may endeavour to find when approaching some problem, is often slight. A scientist entering such grounds runs the risk of getting lost, losing understanding and only catching the loose tail mentioned above. Secondly, sciences, to make a difference, must impress their importance upon the public and convince scientific and policy institutions in order to obtain the means to carry out their mission. The editors consider that there has been progress, and that this book is a sign of such progress, and hope that it provides a further contribution to such advancement. Their hope is that this book will also foster co-operation among those approaching this area from dissimilar disciplines and scientific traditions, and that it will stimulate progress for all scientists advancing on the international road to global sustainability.
A Psychological View on Industrial Transformation and Behaviour -- Sociological Perspectives for Industrial Transformation -- Industrial Transformation and International Law -- Contributions to Transformation Research from Political Science -- Ecologicl Economics and Industrial Trnasformation -- An Evolutionary Economics Perspective in Industrial Transformation -- A Neo-Classical Economic View on Technological Transitions -- Multi-Level Perspective on System Innovation: Relevance for Industrial Transformation -- Managing Transitions for Sustainable Development -- Discussion and Conclusions.
Keywords: History; Environmental law; Environmental policy; Environmental management; Economic history; Development economics; Environmental economics; Economics; Economic History; History, general; Environmental Management; Environmental Economics; Environmental Law/Policy/Ecojustice.; Development Economics; Electronic books